Pengembangan Gel Antiseptik Tangan Mengandung Minyak Atsiri Jeruk Lemon Menggunakan Metode Mikroemulsi Gel - Husni, Patihul; Cahya Lestari, Riska; Hartono, Kusdi (JURNAL FARMASI GALENIKA, 2024)
Hand antiseptic gel preparation is a product that is widely used to protect the body from the entry of bacteria through the hands because of its practical use. Lemon peel (Citrus limon (L) Burm. F) contains essential oils that can inhibit the growth of bacteria so it can be used as a natural antiseptic. This research is aimed at obtaining the best formula preparation of hand antiseptic gel containing lemon essential oil (Citrus lemon (L) Burm. F). The microemulsion formula of lemon essential oil is optimized by making variations in the concentration of surfactant (Tween 80) and cosurfactant (propyleneglycol dan glycerin) which is then formulated into gel dosage form by using a variation in the concentration of the gelling agent. The preparation of the gel carried out a physical stability test that included organoleptic testing, homogeneity, pH, and viscosity. The optimization result of the best microemulsion formula is a formula with a Tween 80 as a surfactant and propylene glycol as a cosurfactant. Hand antiseptic gel preparation containing lemon essential oil (Citrus limon (L) Burm. F) with formula F2 is the best preparation because it is more stable according to the physical stability test of the preparation.